KEPERCAYAAN CALON GURU SEBAGAI FAKTOR KEBERHASILAN PEMBELAJARAN BERPUSAT PADA SISWA - Anis Samrotul Lathifah; Yuswa Istikomayanti; Zuni Mitasari (Universitas Tribhuwana Tunggadewi, 2021)
This study aims to describe teacher beliefs and see the perspective of prospective teachers in implementing microteaching practices through Lesson Study activities, especially implementing student-centered learning. This survey research involved 33 students in the fourth and third years as research subject. Data collection on the self-confidence of prospective teachers through filling out questionnaires and the results of observations made in the Basic Teaching Skills class and Field Work Practice Activities. Qualitative analysis methods and quantitative data grouping are used to determine the response of pre-service teachers in self-confidence in implementing student-centered learning. The result is that the self-confidence of prospective teachers is still at level 2 (instructive) to level 4 (responsive) both in the aspect of confidence in the student-centered learning process and the aspect of trust in building knowledge by students. The highest level of self-confidence of prospective teachers, at 5 level (reformation) has not been achieved. Through an analysis of prospective teachers' self-confidence in these aspects, it can be used as a benchmark whether the learning process is student-centered or still teacher-centered